Influence of environmental factors on seed germination and seedling emergence of yellow sweet clover (Melilotus officinalis) - Ghaderi-Far,F (2010)
Laboratory and greenhouse experiments were conducted to determine the effects of drought and salinity stress, temperature, pH and planting depth on yellow sweet clover (Melilotus officinalis) germination and emergence. Base, optimum and ceiling germination temperatures were estimated as 0, 18.47 and 34.60 ºC, respectively. Seed germination was sensitive to drought stress and completely inhibited at a potential of -1 MPa, but it was tolerant to salinity. Salinity stress up to 90 mM had no effect over the M. officinalis seed germination, but the germination decreased by increasing the salt concentration. The drought and salinity required for 50% inhibition of maximum germination were 207 mM and -0.49 MPa, respectively. High percentage of seed germination (>92%) was observed at pH = 5-6 and decreased to 80% at acidic medium (pH 4) and to 42% at alkaline medium (pH 9) pH. Maximum seedling emergence occurred when the seeds were placed at 2 cm depth and decreased when increasing the depth of planting; no seed emerged from depths of 10 cm.